2022
DOI: 10.3389/fimmu.2022.1001444
|View full text |Cite
|
Sign up to set email alerts
|

Current progress and future perspectives of neoadjuvant anti-PD-1/PD-L1 therapy for colorectal cancer

Abstract: Immunotherapies, especially the programmed cell death 1/programmed cell death ligand 1 (PD-1/PD-L1) inhibitors, have revolutionized the therapeutic strategies of various cancers. As for colorectal cancer (CRC), the current clinical application of PD-1/PD-L1 inhibitors are mainly used according to the mutation pattern, which is categorized into deficient mismatch repair (dMMR)/high levels of microsatellite instability (MSI-H) and proficient mismatch repair (pMMR), or non-high levels of microsatellite instabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 93 publications
0
18
1
Order By: Relevance
“…Specifically, the use of immune checkpoint inhibitors (ICIs), such as CTLA4, PD-1, PD-L1, MSI-H, or dMMR, received much attention. These markers can predict the response to immunotherapy in CRC treatment ( 44 46 ). Furthermore, drug sensitivity analysis revealed that the low-risk group displayed increased susceptibility to oxaliplatin and dabrafenib.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the use of immune checkpoint inhibitors (ICIs), such as CTLA4, PD-1, PD-L1, MSI-H, or dMMR, received much attention. These markers can predict the response to immunotherapy in CRC treatment ( 44 46 ). Furthermore, drug sensitivity analysis revealed that the low-risk group displayed increased susceptibility to oxaliplatin and dabrafenib.…”
Section: Discussionmentioning
confidence: 99%
“…5 ). Additionally, immune checkpoint inhibitors (ICIs) effective for CRC patients when the genetic phenotypes are mismatch-repair-deficient or microsatellite instability-high (dMMR/MSI-H) [ 29 ]. Recent studies have shown that PPARG induces programmed cell death ligand 1 (PD-L1) expression in CRC [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…PD-1/PD-L1 inhibitors are currently the most focused immunotherapies and have achieved brilliant results in various tumor types ( 8 , 82 ). Intratumoral injections can likewise reduce systemic immune adverse effects while ensuring better efficacy.…”
Section: Intratumoral Ablative Agents and Immunotherapy Drugsmentioning
confidence: 99%